KEMAMPUAN REAGEN CURCUMAX MENDETEKSI BORAKS DALAM BAKSO YANG DIREBUS - , ERNA DWI ASTUTI, Dr. drh. Widagdo Sri Nugroho, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Borax is a harmful chemical to health often used in meatball preservation. Development of practical borax detection equipment is needed. Curcumax reagent, an equipment to detect borax, is developed from previous borax detection equipment with turmeric extract. This study aims to determine accuracy the sense of sight and spectrophotometer in detected borax in boiled meatballs and determine the effect of boiling on the borax concentration in the meatballs. This study was using meatballs group as a control and another meatballs group preserved with borax 0,5%, and each meatballs group was boiled in 0, 5, 10 and 15 minutes. Each treatment unit contained five meatballs and the treatment was repeated three times. Laboratory test to detect borax was done be extracting meatballs with ethanol 2 parts and put some drops of Curcumax reagent 1 part. The presence level of borax in the meatballs was known based on the color change of meatballs became orange. Each treatment unit (contained five meatballs) percentage change was made to be analyzed. Spectrophotometer was used to measure the color intensity of meatballs extract. Wave length used on the spectrophotometer was 570 nm. Data was analyzed with ANOVA and followed by LSD (Least Significant Difference) analysis. Borax detection based on sight sense to color change giving an inconsistence result. Color change measurement based on spectrophotometer was more accurate. Boiling process can reduce borax consistence in the meatballs. Curcumax reagent is able to detect borax in the meatballs boiled until 15 minutes.